Branding a digital project for tourism industry through digital marketing - Sukisno S Riadi; Agus Prasojo; Aditya Permana; Andre Putra Sanjaya; Lufiyandi Supriatman (ABDIMU, 2022)
With the introduction of advanced Internet technologies, new channels for reaching target audiences have emerged. Digital branding is now an integral component of all businesses, regardless of size or industry. The increasing importance of digital branding has altered how businesses promote their products to both existing and prospective customers. In the tourism industry, where customers have instantaneous access to information about the most recent deals and lowest prices, the need for digital branding is greater than ever. Today, digital branding is indispensable to the success of all tourism-related businesses. This paper investigates the fundamental determinants of digital branding and their significance in the tourism industry.